Nanoantenna arrays as diode‐less rectifiers for energy harvesting in mid‐infrared band. Issue 2 (21st December 2018) - Chekini, Amir; Sheikhaei, Samad; Neshat, Mohammad
Abstract: Unlike the solar energy, infrared radiation from black bodies around us is always available. In this paper, a novel energy harvesting device is proposed for absorption of the infrared radiation from hot objects around us at temperatures beyond 300 K, in the vicinity of 10 μm wavelength, or from the Earth itself. Electron field emission from sharp edges in vacuum, based on Fowler‐Nordheim (FN) theory, is proposed as a means of rectification. A large number of nanoantennas are placed in an array to achieve high electric field, required for FN electron emission. The issue of wave spatial coherence is discussed in the paper, and it is shown that the device can operate with small affection. Using the proposed device, the MIM/MIIM diode, which is usually used for rectification and has a very low efficiency, is avoided and therefore efficiency is highly improved. A planar spiral series nanoantenna array (SSNA) is designed, as an example, to demonstrate the concept. Bowtie and cross bowtie antenna geometries are considered and their performances are compared.